Penerapan Metode AHP dalam Sistem Pendukung Keputusan Seleksi Penerima Beasiswa Berbasis Multi-Kriteria - Heru Purwanto (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2026)
There are many aspects that must be considered, ranging from academic grades, family economic conditions, to student activity in the organization. When all of this is assessed without a structured approach, the results can feel less consistent. From there, there is a need to use a more systematic method, one of which is the Analytic Hierarchy Process or AHP, which in this study is used to help determine the priorities of scholarship recipients more rationally. The approach used is quantitative, with a multi-criteria decision-making framework. The data was collected through direct observation in the campus environment, then deepened with a paired comparison questionnaire filled out by parties involved in the selection process. After that, the analysis is carried out gradually. Starting from compiling a decision hierarchy, then calculating the priority weight using eigenvectors, to finally checking the consistency of the assessment through the Consistency Ratio. In this part, there are sometimes small doubts about whether all the assessments are really stable, but that's what makes the process feel more controlled. The results obtained show something quite interesting. Academic achievement turned out to be the most dominant criterion compared to others, and directly affected the final results of the selection. From the AHP calculation, one candidate emerged with the highest score of 0.6127, which placed him as the most deserving scholarship recipient.